Diarrea por Campylobacter fetus jejuni y otros agentes infecciosos en niños del área rural de Puriscal, Costa Rica - Vives, Marcela; Mata, Leonardo; Castro, Bernardo; García, María Eugenia; Jiménez, Patricia; Simhon, Alberto (Revista de Biología Tropical, 1984)
Between September 1979 and September 1981 a field study was conducted on the etiology of diarrheal disease in the area of Puriscal, Costa Rica. The presence of enteric pathogens was investigated in the stools of 267 diarrheic children and 190 healthy contrals. 80th groups belong to yearly cohorts recruited at birth as part of a longitudinal multidisciplinary study of mothers and children. Campylobacter fetus jejuni was identified as the only pathogen in the stools of 24 diarrheic children (9%) and in four healthy controls (2%), a significant difference (p< 0,05). The clinical features of the episodes were: irritability (77%), blood in stools (35%), anorexia (38,5%), and fever and vomiting (36%). Dehydration was not important among infected children (only one with 5% dehydration). AH children received oral salt solutions and only two were treated with antibiotics. Rotaviruses were the main etiologic agents (17%) and Campylobacter ranked second (10,5%). The frecuency of enterotoxigenic Enterobacteriaceae was similar in sick children and in controls (10% and 12% respectively).